Functional data analysis of joint coordination in the development of vertical jump performance - Harrison, A. J.; Ryan, W.; Hayes, K. (Sports Biomechanics, 2007)
Mastery of complex motor skills requires effective development of inter-segment coordination patterns. These coordination patterns can be described and quantified using various methods, including descriptive angle-angle diagrams, conjugate cross-correlations, vector coding, normalized root mean squared error techniques and, as in this study, functional data analysis procedures. Lower limb kinematic data were obtained for 49 children performing the vertical jump. Participants were assigned to developmental stages using the criteria of Gallahue and Ozmun (2002). Inter-segment joint coordination data consisting of pairs of joint angle-time data were smoothed using B-splines and the resulting bivariate functions were analysed using functional principal component analysis and stepwise discriminant analysis. The results of the analysis showed that the knee-hip joint coordination pattern was most effective at discriminating between developmental stages. The results provide support for the application of functional data analysis techniques in the analysis of joint coordination or time series type data.